Jesuit Writers’ Critique of Tyranny and Conquest in the School of Salamanca - Senent de Frutos, Juan Antonio (Journal of Jesuit studies, 2025)
This article examines tyranny and injustice in the New World within the doctrinal framework of the School of Salamanca and in Jesuit practice. It situates the critique in Salamanca’s natural‑law tradition, in which political power arises from the community, is ordered to the common good, and is limited by reason and law. Building on Aquinas’s account of tyranny as usurpation and abuse, Francisco de Vitoria extends the analysis to inter‑polity relations through the ius communicationis and a world conceived as a republic, which delegitimates conquest and distinguishes legitimate rule by orientation to the common good. Bartolomé de las Casas radicalizes the critique by rejecting forced conversion, the encomienda, and any "right of conquest." Jesuit Scholastics consolidate these positions: Luis de Molina affirms the political and property rights of indigenous nations; Francisco Suárez universalizes the natural legislative power of all peoples and underscores the parity of Christian and non‑Christian princes; and José de Acosta denounces tyrannus ab usu among colonial governors who scandalize the Gospel. Jesuit ordinances for the Paraguayan reducciones institutionalize consent: rejecting personal service and malocas, learning Guaraní, limiting burdens, respecting the authority of caciques, and organizing communal life to protect basic goods and shared dominion.